2009
DOI: 10.1016/j.envpol.2009.05.005
|View full text |Cite
|
Sign up to set email alerts
|

An integrated tool to assess the role of new planting in PM10 capture and the human health benefits: A case study in London

Abstract: We recommend you cite the published version. The publisher's URL is http://dx.doi.org/10. 1016/j.envpol.2009.05.005 Refereed: Yes This is a preprint of an article published in Environmental Pollution c 2009 ?copyright Elsevier?. Environmental Pollution is available online at: http://www.elsevier.com/wps/find/journa Disclaimer UWE has obtained warranties from all depositors as to their title in the material deposited and as to their right to deposit such material. UWE makes no representation or warranties of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
105
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(114 citation statements)
references
References 44 publications
(37 reference statements)
6
105
0
2
Order By: Relevance
“…Trees help purify the air and reduce rates of asthma and other respiratory illnesses in urban populations [57,58]. When we fall ill, or are convalescing from illness, trees can play a pivotal role in healing.…”
Section: A Suite Of Urban-forest Valuesmentioning
confidence: 99%
“…Trees help purify the air and reduce rates of asthma and other respiratory illnesses in urban populations [57,58]. When we fall ill, or are convalescing from illness, trees can play a pivotal role in healing.…”
Section: A Suite Of Urban-forest Valuesmentioning
confidence: 99%
“…Trees have been found effective in PM removal in cities (Escobedo et al, 2011;McDonald et al, 2007;Tiwary et al, 2009). This has led to new urban tree planting programs, prioritizing tree species selection with greater pollution mitigation potential, alongside choosing strategic locations for their optimal outcomes (Calfapietra et al, 2013;Llausàs and Roe, 2012;Morani et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies that have linked removal and health effects include one in London where a 10 Â 10 km grid with 25% tree cover was estimated to remove 90.4 t of PM 10 annually, which equated to the avoidance of 2 deaths and 2 hospital admissions per year (Tiwary et al, 2009). In addition, Nowak et al (2013) reported that the total amount of PM 2.5 removed annually by trees in 10 U.S. cities in 2010 varied from 4.7 t in Syracuse to 64.5 t in Atlanta.…”
Section: Introductionmentioning
confidence: 99%